Abundance and diversity of terrestrial free-living nematodes in potato agroecosystem - MUTALA’LIAH MUTALA’LIAH; ABDUL MANAN; LAFI NA’IMATUL BAYYINAH (Nusantara Bioscience, 2023)
Abstract. Mutala’liah, Manan A, Bayyinah LN. 2023. Abundance and diversity of terrestrial free-living nematodes in potato agroecosystem. Nusantara Bioscience 15: 129-136. The presence of terrestrial free-living nematodes in agroecosystems is frequently overlooked. However, these microorganisms in agroecosystems soil are beneficial for supporting plant growth. These microorganisms could recycle the nitrogen in soil, decomposition and mineralization of organic matter, and suppress the densities of plant parasitic nematodes through their life strategy. Terrestrial free-living nematodes are classified according to trophic groups such as bacterivores, fungivores, predators, and omnivores. Reports on the abundance and diversity of terrestrial free-living nematode populations in agroecosystems, especially on potato plantations, were limited. They usually focused on the plant parasitic nematode’s attack on potatoes. Therefore, this study aimed to examine the diversity and abundance of terrestrial free-living nematodes in potato agroecosystems. The current study was conducted in two potato fields in Pratin Village, Serang, Purbalingga, Central Java, Indonesia. Soil samples were collected from two potato fields planted with different varieties (Granola and Atlantik) and extracted using the Whitehead-tray method. The variables observed were the diversity of genera and the abundance of terrestrial free-living nematode populations from each field. Population density data were analyzed by T-test, and diversity (H'), evenness (E), and dominance index (D) were also calculated. The results showed that the mean population densities of terrestrial free-living nematodes in the two fields were significantly higher at 918.40 individuals/ 100 g of soil in the Atlantik field than in the Granola field 76.53 individuals/ 100 g of soil. However, the diversity, evenness, and dominance index were not significantly different in both fields. Genera of nematode found in the Granola field were Diplogaster, Dorylaimus, Trypilla, and Lotonchus, while in the Atlantik field were Rhabditis and Dorylaimus.